2017
DOI: 10.2166/wst.2017.061
|View full text |Cite
|
Sign up to set email alerts
|

From biofilm ecology to reactors: a focused review

Abstract: Biofilms are complex biostructures that appear on all surfaces that are regularly in contact with water. They are structurally complex, dynamic systems with attributes of primordial multicellular organisms and multifaceted ecosystems. The presence of biofilms may have a negative impact on the performance of various systems, but they can also be used beneficially for the treatment of water (defined herein as potable water, municipal and industrial wastewater, fresh/brackish/salt water bodies, groundwater) as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
61
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(63 citation statements)
references
References 65 publications
1
61
0
1
Order By: Relevance
“…Applying different ratios between the flowrates of the concentrated wastewater and tap water allowed us to operate MBBRs with favorable values of hydraulic retention times (HRTs) and influent's COD. A glance through the literature indicates that MBBRs have been so far operated in a wide range of HRTs (Boltz et al, 2017;McQuarrie and Boltz, 2011;Rusten et al, 2006) and a definitive value has not stablished yet, in particular, for tertiary MBBRs which are in the beginning steps of the attention. However, in the continuous running of the set-up, HRTs and influent's COD values were stepwisely changed from 20 to 4 h and 500 to 100 mg•L −1 , respectively.…”
Section: Mbbr Set-upmentioning
confidence: 99%
See 1 more Smart Citation
“…Applying different ratios between the flowrates of the concentrated wastewater and tap water allowed us to operate MBBRs with favorable values of hydraulic retention times (HRTs) and influent's COD. A glance through the literature indicates that MBBRs have been so far operated in a wide range of HRTs (Boltz et al, 2017;McQuarrie and Boltz, 2011;Rusten et al, 2006) and a definitive value has not stablished yet, in particular, for tertiary MBBRs which are in the beginning steps of the attention. However, in the continuous running of the set-up, HRTs and influent's COD values were stepwisely changed from 20 to 4 h and 500 to 100 mg•L −1 , respectively.…”
Section: Mbbr Set-upmentioning
confidence: 99%
“…In spite of this fact, recently, moving bed biofilm reactors (MBBRs) are under the sharp-eyed investigation to see their capability in tertiary treatment of wastewater (Tang et al, 2017a(Tang et al, , 2017b. Indeed, the acceptable performance of these versatile reactors have been already proved for carbon oxidation, nitrification, denitrification, and deammonification (Boltz et al, 2017;McQuarrie and Boltz, 2011;Rusten et al, 2006). In addition, Torresi et al (2016) have lately noticed high potential of tertiary nitrifying MBBRs in MPs removal.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the activated sludge, the biofilm is less susceptible to the changes of such technological parameters as: contaminants load, volume of inflowing wastewater or presence of toxic substances in wastewater. This is due to high quantities of extracellular polymeric substances (EPS) which constitute a buffer to microorganisms [Boltz et al 2017, Nicolella et al 2000b. As a result of long period of biomass retention in a reactor, the biofilm is characterized by a higher degree of mineralization and, thus, by a lower volume of excess biomass discharged from the reactor.…”
Section: Introductionmentioning
confidence: 99%
“…Biofilms are self‐assembling, result in high cell concentrations, and can increase the operational lifetime of a reactor by obviating the need to restart the reactor. Numerous applications of biofilm reactors have been successful in wastewater treatment . Several studies have reported improvements in productivity and yield using biofilms for fermentative production of commodity chemicals, including, for example, up to 400% improvement in lactic acid productivity using a repeated batch biofilm system …”
Section: Introductionmentioning
confidence: 99%